Karakteristik Susut Beton Dengan Alwa Murni - Indri Soliyansyah; Euis Kania Kurniawati; Tahadjuddin Tahadjuddin (SANTIKA is a scientific journal of science and technology, 2017)
Shringkage is one of the important concrete properties which, decreasingdurability of concrete and causeing concrete cracking. The shrinkage willdepend on aggregate selected. In this researd used a pute alwa aggregate whichmade from expanded clay burned in rotary kiln at high temperature (>6000C).Alwa has a rough surface shape, high absorption that allows aggregate to storewater needed for concrete hydration which can be removed from the shrinkage.This analysis uses experimental methods, and uses mortar specimens with 5x5x5cm cubes. Mixed mortar design using the DoE method and for testing in test arecompressive strength, porosity, and shrinkage of concrete. The results show that concrete mortar using alwa enough effective to reduceshrinkage with optimum addition of 18% for 20 - 30% percent did not meet thecompressive strength of the planned.